2020
DOI: 10.1128/mbio.02528-20
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a New Neisseria gonorrhoeae Type IV Pilus Assembly Factor, TfpC

Abstract: Neisseria gonorrhoeae relies on type IV pili (T4p) to promote colonization of their human host and to cause the sexually transmitted infection gonorrhea. This organelle cycles through a process of extension and retraction back into the bacterial cell. Through a genetic screen, we identified the NGO0783 locus of N. gonorrhoeae strain FA1090 as containing a gene encoding a protein required to stabilize the type IV pilus in its extended, nonretracted conformation. We have named the gene tfpC and the protein TfpC.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…gonorrhoeae strain FA1090 pilin variant 1-81-S2 (confirmed using primers pilRBS and SP3A ( Table 3 ) [ 67 ]). N-1-60 carries multiple point mutations in the pilE guanine quadruplex sequence upstream of pilE [ 68 ] (confirmed with primers USS2 and pilAREV [ 66 ] ( Table 3 )) and the phase-locked “on” pilC2 (NGO0055) sequence (confirmed using primers pilCfor and pilCdownstream ( Table 3 )), not pilC1 as previously indicated [ 66 ]. For all strains, the 1-81-S2 pilE sequence was confirmed in PCR products using primers pilRBS and SP3A ( Table 3 ) in addition to the non-variable guanine quadruplex and the phase-locked pilC 2.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…gonorrhoeae strain FA1090 pilin variant 1-81-S2 (confirmed using primers pilRBS and SP3A ( Table 3 ) [ 67 ]). N-1-60 carries multiple point mutations in the pilE guanine quadruplex sequence upstream of pilE [ 68 ] (confirmed with primers USS2 and pilAREV [ 66 ] ( Table 3 )) and the phase-locked “on” pilC2 (NGO0055) sequence (confirmed using primers pilCfor and pilCdownstream ( Table 3 )), not pilC1 as previously indicated [ 66 ]. For all strains, the 1-81-S2 pilE sequence was confirmed in PCR products using primers pilRBS and SP3A ( Table 3 ) in addition to the non-variable guanine quadruplex and the phase-locked pilC 2.…”
Section: Methodsmentioning
confidence: 77%
“…Strains used in this study are listed in Table 2 . The parental strain N-1-60 [ 66 ] is N . gonorrhoeae strain FA1090 pilin variant 1-81-S2 (confirmed using primers pilRBS and SP3A ( Table 3 ) [ 67 ]).…”
Section: Methodsmentioning
confidence: 99%
“…For initial validation experiments, hits showing complementarity between the predicted sRNA single stranded region and the mRNA region comprising RBS and start codon were taken into consideration (Tables S3 and S4). NGFG_01006 encoding the type IV pilus biogenesis factor TfpC [52] and NGFG_00693 encoding an aminotransferase were the only hits meeting these criteria which scored in the outcome of both in silico target prediction tools. However, no significant differences in the transcript amounts of tfpC and NGFG_00693 were observed in qRT-PCR experiments performed on RNA extracted from MS11 wild-type and the sRNA deletion mutant MS11 ΔtfpR1.…”
Section: Resultsmentioning
confidence: 99%
“…TfpC, which was only recently identified as a new type IV pilus biogenesis factor, is located in the periplasm and harbours an N-terminal transmembrane domain anchoring the protein to the inner membrane. Deletion of tfpC resulted in nonpiliated colony morphology and reduced transformation competence and it was hypothesized that TfpC stabilizes the pilus in its extended conformation [52]. mRNA quantification indicated that NGFG_01479, encoding the minor pilin PilV [72], is controlled by TfpR1 as well (, ).…”
Section: Discussionmentioning
confidence: 99%
“…Although cryo-ET has not been used to study the CU pathway, it has been successfully implemented to elucidate the low-resolution features of T4P and T2SS pseudo-pilus assembly devices (Gold et al, 2015;Chang et al, 2016;Ghosal et al, 2019). Work on the T4P systems has revealed pilus structures emanating into the extracellular space (Gold et al, 2015;Chang et al, 2016) and with the expected future increases in cryo-ET resolution, as discussed above, in the future cryo-ET may be able to provide greater detail of how these pili form at the membrane and the role of pilus-specific assembly factors in their biogenesis (Hu et al, 2020). Cryo-EM has had a major impact on the of study filamentous systems over the past decade and it will be interesting to see how EM and its incorporation with other approaches (e.g.…”
Section: Discussionmentioning
confidence: 99%